PEMANFAATAN AIR CUCIAN BERAS UNTUK PEMBUATAN PUPUK ORGANIK DI DESA KENINE KABUPATEN BENER MERIAH - Anshar, Khairul; Muhammad; Ginting, Zainuddin; Muarif, Agam; Mulyawan, Rizka; Meiyanti, Rini (Aptekmas Jurnal Pengabdian pada Masyarakat, 2024)
Rice washing water is generally not used and considered as waste. The elements contained in rice washing water are nutrients needed for plants. From this fact, rice washing water waste has the potential to be used as liquid organic fertilizer for plants. In general, rice washing water from households in Kenine Village, Wih Pesam District, Bener Meriah Regency is disposed of without being used properly, such as being thrown away or directly watered on plants. On the one hand, the area is increasingly using inorganic fertilizers on plants, including the main commodity crop, namely coffee. Based on these problems, community service activities were carried out in Kenine Village, Bener Meriah Regency through counseling activities to make organic fertilizer for the village community to use rice washing water waste as the main ingredient with molasses and EM4 as an alternative solution to the use of commercial chemical fertilizers which are much more economical and secure from the organic side.